Health effects of using popular alternatives to smoking - a review of the literature - Oronowicz, Radoslaw; Kmiotek, Weronika; Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Karuś, Aleksandra; Jama, Grzegorz; Staszczak, Paweł; Jaworska, Barbara; Ragan, Dagmara; Długosz, Joanna (Quality in Sport, 2024)
Introduction and Purpose: More and more alternatives to traditional smoking are available on shop shelves. Are other ways of using nicotine healthier for us? What are the advantages and disadvantages? The aim of this article is to trace the health effects of new, popular alternatives to the traditional cigarette. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: “Iqos”, “Glo”, „ e-cigarette” and „ tobacco” appropriate configurations. Conclusions: Modern tobacco devices, such as IQOS and Glo, emit significantly less harmful substances than traditional cigarettes. In particular, emissions of carbon monoxide, formaldehyde and polycyclic aromatic hydrocarbons are significantly lower. Nevertheless, nicotine remains the main ingredient in these products, with serious health risks. Regular use of nicotine can lead to addiction, cardiovascular disease and problems with the nervous system and oral cavity. Inhaling aerosol from tobacco devices such as IQOS, Glo and disposable e-cigarettes can lead to damage to lung cells and other respiratory health problems. Despite the lower risks, the use of alternative smoking methods is still harmful to our health.